Cuidados de enfermería ambulatoria en paciente pediátrico con tetralogía de Fallot. a propósito de un caso - Mingo Narváez, Katty Valeria; López Ayala, Anyela Lisbeth (My University, 2024)
Tetralogy of Fallot (TF) is one of the most common and severe congenital heart diseases. This disease is multifactorial in origin and has a significant impact on the physical, emotional and social health of pediatric patients and their families. Objective: To design a comprehensive nursing care plan based on the Nola Pender model for managing pediatric patients with TF, which aims to strengthen the family's adaptation to the management of individualized strategies for the pediatric patient.Methodology: The research was designed as a descriptive and analytical study, focused on a pediatric patient with this diagnosis, resident of the Santa Rosa canton, who receives outpatient care, to obtain data, the review of the medical history, the collection of information on visits, perception of care at home were used, this methodology seeks to provide a comprehensive view of outpatient nursing care in pediatric patients, Results: The relevance of continuous monitoring of vital signs, prevention of hypoxemic crises and family education on the management of critical episodes was highlighted, interventions include hemodynamic monitoring, pain management, early detection of complications and emotional support, based on the Nola Pender model, healthy habits were promoted and the study aims to instruct the family, providing a deeper understanding of the needs, experiences to prevent long-term complications. Conclusions: Nursing plays an essential role in the comprehensive care of TF, the use of the Nola Pender model proved to be effective in improving the patient's quality of life and facilitating family adaptation
La Tetralogía de Fallot (TF) es una de las cardiopatías congénitas más frecuentes y severas, esta enfermedad es de origen multifactorial, presenta un impacto significativo en la salud física, emocional y social de los pacientes pediátricos y sus familias. Objetivo: Diseñar un plan integral de cuidados de enfermería ambulatorio basado en el modelo de promoción de Nola Pender para el fortalecimiento de la adaptación de la familia en el manejo del paciente con TF. Metodología: s Se destacó la relevancia del monitoreo continuo de signos vitales, prevención de crisis hipoxémicas y la educación familiar sobre el manejo de episodios críticos, las intervenciones incluyen vigilancia hemodinámica, manejo del dolor, detección temprana de complicaciones y apoyo emocional, basado en el modelo de Nola Pender, se promovieron hábitos saludables y el estudio tiene como objetivo instruir a la familia, brindando una comprensión más profunda a las necesidades, experiencias para prevenir complicaciones a largo plazo. Conclusiones: La enfermería juega un papel esencial en el cuidado integral de la TF, el uso del modelo de Nola Pender demostró ser eficaz para mejorar la calidad de vida del paciente y facilitar la adaptación familiar.
Keywords: TETRALOGIA DE FALLOT; INTERVENCION DE ENFERMERIA; TEORIA DE NOLA PENDER